2004
DOI: 10.1023/b:abme.0000012745.05794.32
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Finite Element Analysis of Residual Stress in Arteries

Abstract: Calculation of residual stress in arteries, using the analytical approach has been quite valuable in our understanding of its critical role in vascular mechanics. Stresses are calculated at the central section of an infinitely long tube by imposing a constant axial stretch while deforming the artery from the stress-free state to its unloaded state. However, segments used to perform opening-angle measurements have finite lengths. Further, the stress-free artery configuration is assumed to be circular. Experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 9 publications
2
51
0
Order By: Relevance
“…Rachev 1997;Rachev & Hayashi 1999;Holzapfel et al 2000;Humphrey 2002, ch. 7;Raghavan et al 2004;Ohayon et al 2007). Similar comments apply to the work of Olsson et al (2006), who *Author for correspondence (rwo@maths.gla.ac.uk).…”
Section: Introductionmentioning
confidence: 79%
“…Rachev 1997;Rachev & Hayashi 1999;Holzapfel et al 2000;Humphrey 2002, ch. 7;Raghavan et al 2004;Ohayon et al 2007). Similar comments apply to the work of Olsson et al (2006), who *Author for correspondence (rwo@maths.gla.ac.uk).…”
Section: Introductionmentioning
confidence: 79%
“…In reality, a zero-stress state does not exist in vivo, however, it was found that the magnitude of residual stresses were negligible (up to 3 kPa [34]) in comparison with the aortic root stresses observed at the peak pressure. However, it must be acknowledged that residual stresses and strains act in homogenising the stress field in the arterial wall and allows greater compliance [35].…”
Section: Limitationsmentioning
confidence: 93%
“…In Fung, 90 the stretch ratio in rabbit arteries varies from 1.6 in the carotid to 1.4 for the upper abdominal aorta, whereas Fung and Liu 91 showed that the opening angle in normal rats varies from 160掳 in the ascending aorta and 90掳 in the arch to 60掳 in the thoracic region. Details of the use of these parameters for the modeling of the vessel properties are not discussed here, but the reader can refer to Lee et al, 92 Holzapfel et al, 93 or Raghavan et al 94 for additional information on this issue. Concerning the variation of the elastic properties as a function of the load applied (pressure, tension, and flow, for instance), one can refer to Martinez et al 95 and Lee et al 92 In these papers, the authors measure the evolution of the longitudinal and circumferential stretch ratio as a function of internal pressure during an inflation test.…”
Section: Solid Physical Propertiesmentioning
confidence: 99%